Photocatalytic Mechanism and Charge Transfer of PtS2/WSe2 Heterostructures：First-principles Study - Sun, Zhaonan; Song, Yuxuan; Lv, Wendi; Zeng, Xiangyu; Fu, Zhongtian (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
To address the recombination problem of photogenerated electrons and holes during photocatalysis, strategies to design composite photocatalysts with heterojunction structures have been widely adopted. In order to explore the electron transfer pathway and photocatalytic mechanism of the PtS2/WSe2 heterostructure, the band structure, electronic properties and catalytic activity of the structure were systematically calculated by density functional theory (DFT). We designed two models consisting of PtS2 and WSe2 monolayers to find more stable structures through adsorption energy calculations. In this work, MUlliken charge analysis and differential charge density confirmed the heterojunction as an S-scheme heterojunction. Due to the height difference between the Fermi levels of the two pristine semiconductors, electrons flow from WSe2 to PtS2 to form a built-in electric field and band bending. The properties of the S-scheme heterojunction allow the heterostructure to possess a suitable band gap without losing the redox ability, thereby ensuring that the PtS2/WSe2 heterostructure can spontaneously undergo HER and OER processes of water splitting. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).